2015
DOI: 10.4172/1747-0862.s4-005
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles for Generating Novel Systems for Better Applications: A Review

Abstract: The environmental sustainability and use of environmentally acceptable biomaterials are major areas of scientific and industrial research. In recent times, identification and application of suitable biopolymers instead of petroleum derived conventional polymers are gaining more attention. Chitosan and chitosan derived nanoparticles and nanocomposites are very promising due to their versatile properties and have found applications in various areas such as biomedical, foods, food packaging and personal care. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…Chitosan is a biodegradable, biocompatible natural polysaccharide polymer with immunological, antibacterial, and wound healing characteristics [19,20]. According to Radhakrishnan et al [21], the edible film of chitosan was found to delay water loss, suppress microbial growth, and preserve the color of papaya, mango, and strawberries. Furthermore, chitosan film retarded enzymatic browning and discoloration in cut pieces of apple [22] and mushroom [23].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a biodegradable, biocompatible natural polysaccharide polymer with immunological, antibacterial, and wound healing characteristics [19,20]. According to Radhakrishnan et al [21], the edible film of chitosan was found to delay water loss, suppress microbial growth, and preserve the color of papaya, mango, and strawberries. Furthermore, chitosan film retarded enzymatic browning and discoloration in cut pieces of apple [22] and mushroom [23].…”
Section: Introductionmentioning
confidence: 99%